Lesser Flamingos Descendants of Phoenix - Krienitz, Lothar (Springer Berlin Heidelberg, 2018)
This book provides insights into the fascinating life of the Lesser Flamingo (Phoeniconaias minor) and describes how this enigmatic bird has adapted to the extreme conditions of tropical soda lakes and can even withstand the caustic effects of brine. However, humans are increasingly disrupting the natural cycles of these wetlands, and for these pink birds characteristic of these salt lakes, it is becoming more and more difficult to find suitable habitats, food and breeding grounds. Their fate is considered a cautionary example of man's dealings with nature. Will the Lesser Flamingo survive in a man-made world? Flamingos are considered to be an embodiment of the Phoenix, and the author interweaves his personal experiences with and observations of the flamingos' unusual habitats with the Phoenix motif in order to stimulate reflection on the circle of life. Written in an accessible style that combines science, biological information and the author's own travels and fieldwork, the book also includes a wealth of captivating images. As such, it offers a unique resource for biologists and nature-loving Africa and Asia enthusiasts alike.